Effect of early tirofiban administration on N-terminal pro-B-type natriuretic peptide level in patients treated with primary percutaneous coronary intervention - Fabris, Enrico; Giannitsis, Evangelos (Catheterization and cardiovascular interventions, 2019)
Objectives: To investigate the potential association between early tirofiban treatment and N-terminal pro-B-type natriuretic peptide (NT-proBNP) level after primary percutaneous coronary intervention (PCI). Background: Whether the use of adjunctive early glycoprotein IIb/IIIa inhibitors (GPIs) therapy, may affect the level of NT-proBNP after primary PCI is poorly studied. Methods: Nine hundred and eighty four ST-elevation myocardial infarction (STEMI) patients undergoing primary PCI were randomized to either pre-hospital tirofiban administration or placebo. NT-proBNP levels were evaluated on admission before angiography (baseline) and 18-96 hr after PCI. Results: There were 918 (93.3%) patients with NT-proBNP values available at baseline and 865 (87.9%) post-PCI. Post-PCI NT-proBNP level dichotomized with median value as cut-off (968.8 pg/mL, IQR 430.9-1970.0) was significantly lower in patients treated with early tirofiban as compared to placebo (45.5% vs. 54.2% P = 0.011). At multivariate logistic regression analysis, independent predictors of post-PCI NT-proBNP level above the median were: NT-proBNP baseline level (OR 5.19; 95% CI, 2.92-9.25, P < 0.001), Killip class>I (OR 4.07; 95% CI 1.24-13.36, P = 0.021), anterior infarct location (OR 2.61; 95% CI 1.84-3.70, P < 0.001), age (years) (OR 1.04; 95% CI 1.03-1.06, P < 0.001), male gender (OR 0.38; 95% CI 0.26-0.57, P < 0.001), prior PCI (OR 0.49; 95% CI 0.27-0.90, P = 0.021) and tirofiban administration (OR 0.71; 95% CI 0.51-0.99; P = 0.045). Conclusions: In a large cohort of STEMI patients, pre-hospital tirofiban administration was independently associate with a lower risk of high NT-proBNP level after primary PCI, supporting the potential benefit of early antithrombotic treatment administration in STEMI patients. The trial is registered under No. ISRCTN06195297.